2014
DOI: 10.1016/j.ijid.2014.01.024
|View full text |Cite
|
Sign up to set email alerts
|

First case of Mediterranean spotted fever-associated rhabdomyolysis leading to fatal acute renal failure and encephalitis

Abstract: Mediterranean spotted fever (MSF) is a tick-borne zoonosis caused by Rickettsia conorii. In Italy, about 400 cases are reported every year and nearly half of them occur in Sicily, which is one of the most endemic regions. Although MSF is mostly a self-limited disease characterized by fever, skin rash, and a dark eschar at the site of the tick bite called a 'tache noire', serious complications are described, mainly in adult patients. Nevertheless, severe forms of the disease with major morbidity and a higher mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…Elevated protein levels were found in three cases. The glucose levels were normal in one case, slightly elevated in two, and decreased in one [1, 2, 9]. Of the four who survived, only one patient recovered without sequelae [1, 2, 9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated protein levels were found in three cases. The glucose levels were normal in one case, slightly elevated in two, and decreased in one [1, 2, 9]. Of the four who survived, only one patient recovered without sequelae [1, 2, 9].…”
Section: Discussionmentioning
confidence: 99%
“…The glucose levels were normal in one case, slightly elevated in two, and decreased in one [1, 2, 9]. Of the four who survived, only one patient recovered without sequelae [1, 2, 9]. Although systematic pharmacokinetic studies are lacking for the concentration of doxycycline in CSF against Rickettsia conorii , a study on neuroborreliosis showed that daily doses of 200 mg of doxycycline produce a CSF concentration close to the MICs for susceptible bacteria, both in the absence and in the presence of meningeal inflammation [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, atypical forms can be observed with multiorgan involvement including hepatic, renal, neurological and cardiac impairment. [1][2][3][4] We here in report a difficult diagnosis of rickettsiosis occuring after hemorrhagic fever. We also describe EN-FACE-OCT rickettsiosis retinal findings and emphasize the importance of ocular examination in atypical forms of rickettsiosis.…”
Section: Introductionmentioning
confidence: 88%
“…23 Multiple organ failure as onset of Mediterranean spotted fever days after symptoms' onset. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Other techniques, as isolation of bacteria and/or molecular polymerase chain reaction (PCR) to genome identification, which can be performed on blood, skin biopsies and ticks, are not routinely used because of their complexity and costs. Therefore, in clinical practice, they are reserved only in cases of extremely high clinical suspicion with all the other tests proving negative.…”
Section: Methods Of Researchmentioning
confidence: 99%